Некоторые морфологическиe особенности воробья домового (Passer domesticus L.) па примере запорожской популяции - Самчук, Н.Д. (Вестник зоологии, 1971)
When studying some morphological peculiarities of the Zaporozhie population of Passer domesticus L. it was established that adult males and females as well as adult and young birds differ from each other in some external and internal characters.